Higher education exports in South Africa: A case study of Stellenbosch University - du Plessis, E; Fourie, J (South African Journal of Higher Education, 2011)
International trade in higher education services is one of the fastest growing tradable service sectors globally. Apart from the positive externalities international students create through knowledge mobility and spill-over, campus diversity, and local community development participation, spending by international students in the host city and immediate surroundings add significantly to local economic growth. The aim of this article is to show, firstly, the relative strong growth of South Africa’s higher education exports vis-à-vis other countries. We also find that South Africa has a strong comparative advantage in exporting higher education services. Secondly, we use a pilot questionnaire conducted in 2009 at Stellenbosch University to estimate the economic impact of these students on the local economy. We find that international students contribute between R159 million and R172 million per semester to the local economy, in addition to the positive – but largely unquantifiable – externalities they create.